HBR guide to delivering effective feedback. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2016)
"To help your employees meet their goals and fulfill their potential, you need to provide them with regular feedback. But the prospect of sharing potentially negative news can be overwhelming. How do you construct your message so that it's not only well received but also expressed in a way that encourages change? Whether you're commending exemplary work or addressing problem behavior, the HBR Guide to Delivering Effective Feedback provides you with practical advice and tips to transform any performance discussion--from weekly check-ins to annual reviews--into an opportunity for growth and development. You'll learn to: Establish trust with your direct reports; Assess their performance fairly; Emphasize improvement, even in criticism; React calmly to a defensive feedback recipient; Recognize and motivate star performers; and Create individualized development plans. Arm yourself with the advice you need to succeed on the job, from a source you trust. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges."--! From Amazon.com.
Section 1: Ongoing Feedback. -- Giving effective feedback: the two types of feedback, defined -- Sometimes negative feedback is best: for some, it can be more motivating than praise / Heidi Grant Halvorson -- Giving feedback that sticks: prevent a fight-or-flight response / Ed Batista -- A better way to deliver bad news: take an open approach to your discussion / Jean-François Manzoni -- The set-up-to-fail syndrome: how bosses create their own poor preformers / Jean-François Manzoni and Jean-Lois Barsoux -- How to give feedback that helps people grow: establish trust, then focus on improvement / Monique Valcour -- Recognize good work in a meaningful way: tailor your rewards to the person and the effort / Christina Bielaszka-Duvernay -- Section 2: Formal Performance Appraisals. -- Delivering an effective performance review: five basic ruls for getting it right / Rebecca Knight -- Managing performance when it's hard to measure: focus on the individual, not a rating / Jim Whitehurst -- Stop worrying about your employee's weaknesses: emphasize their strengths to help them grow / Peter Bregman -- How to set and support employee goals: set your people up to succeed / Amy Gallo -- When to grant a promotion or raise: first, make sure they can do the job they want / Amy Gallo -- Tips for record keeping: track performance so reviews run smoothly -- Section 3: Tough Topics. -- How to help and underperformer: identify the problem and see if coaching can help / Amy Gallo -- Delivering criticism to a defensive employee: stick to the facts / Holly Weeks -- How to give star performers productive feedback: discuss performance, new frontiers, and aspirations / Amy Gallo -- Prioritizing feedback-even when time is short: three ways to be more efficient / Daisy Wademan Dowling -- Navigating the choppy waters of cross-cultural feedback: make subtle shifts to adapt your approach / Andy Molinsky -- How to discus
Description based on online resource; title from digital title page (viewed on July 18, 2019).
Master record variable field(s) change: 050
Keywords: Employee retention; Feedback (Psychology); Employees -- Rating of; Personnel management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Employee retention; Employees -- Rating of; Feedback (Psychology); Personnel management; elektronické knihy; electronic books